Language learning strategies of students in content-based instruction - Ahamad Shah, Mohamed Ismail; Ismail, Yusuf; Esa, Zaleha; Muhamad, Ainon Jariah (2010)
This study investigates the learning strategies of students at the International Islamic University Malaysia (IIUM). The study was mainly motivated by concerns about the standards of English of graduates of Malaysian universities. These concerns have also been expressed by the IIUM, one of the few universities in Malaysia using English as the medium of instruction. The primary objective of this research has been to identify what good language learners do to learn a second language. The study investigated frequency of strategy use according to type of courses (i.e. content-based versus non content-based), gender, and proficiency levels. There were 312 students taking English for Occupational Purposes (EOP) and English for Academic Purposes (EAP) courses. Their learning strategies were investigated through an analysis of their responses to Rebecca Oxford’s Strategy Inventory for Language Learning (SILL) (Oxford, 1990), an instrument that has been validated in a number of studies. The study found that the students from the different degree programmes differed in the use of the six different strategies. The study also did not find any significant relationship between language learning strategies and gender.